Blood‐Derived Stem Cells (BDSCs) plasticity: In vitro hepatic differentiation1. Issue 6 (25th February 2013) - Alaimo, Giorgia; Cozzoli, Eliana; Marfe, Gabriella; Esposito, Luca; Ranalli, Marco; Hmada, Dalya; Giordano, Antonio; Gambacurta, Alessandra
Abstract The limited availability of hepatic tissue suitable for the treatment of liver disease and drug research encourages the generation of hepatic‐like cells from alternative sources as support for the regenerative medicine. Human blood derived stem cells (BDSCs) express surface markers and genes characteristic of pluripotent stem cells and have the ability to differentiate into different cell types, including tissues of endodermal origin (i.e., liver). Therefore they can represent a valuable source of hepatocytes for medicine. In this investigation, we exploited a fast hepatic differentiation protocol to generate hepatocyte‐like cells from human BDSCs using only hepatocyte growth factor (HGF) and fibroblast growth factor‐4 (FGF‐4) as growth factors. The resulting cell population exhibited hepatic cell‐like morphology and it was characterized with a variety of biological endpoint analyses. Here, we demonstrate how human BDSCs can be reprogrammed in hepatocyte‐like cells by morphological, functional analysis, reverse transcriptase (RT)‐PCR, and Western Blot assay. This study defines a fast and easy reprogramming strategy that facilitates the differentiation of human BDSCs along a hepatic lineage and provides a framework for a helpful source in the stem cells therapy and liver disorders. J. Cell. Physiol. 228: 1249–1254, 2013. © 2012 Wiley Periodicals, Inc.